Effectiveness of Online Learning Model for Grade I Students of Tlogomulyo State Elementary School - Yuli Wahyuningsih; Uswatun Khasanah; Ayu Nurulita; Umi Rachmawati (Prosiding University Research Colloquium, 2021)
Corona Virus Disease (Covid-19) occurs that almost all countries around the world have amajor impact on almost all aspects of both economic, social, cultural, and even education.Almost all levels of education that were originally done in schools are now directed online.This article aims to explain how effective online learning of 1st graders of Tlogomulyo stateelementary school during a pandemic. The data analysis used in this study is a datacollection, this study uses instruments in the form of observations with the number ofstudents as many as 17 students in grade 1 consisting of 11 men and 6 women. The resultsof the study, showed that Corona Virus Disease (Covid-19) has an impact on theimplementation of online learning in the 1st graders of Tlogomulyo state elementaryschool, which is less effective in the learning process so there needs to be cooperationbetween schools and parents of students in learning at home.